The Importance of Early Referral in Pediatric Acute Liver Failure - Jerónimo, Mónica (2015)
Introduction: Acute liver failure is a rare disorder associated to high morbidity and mortality despite survival improvement through liver transplantation. The importance of a multidisciplinary approach and early referral to a pediatric liver transplantation center were important conclusions of a national meeting in 2008, from which resulted an actuation consensus.Objectives: To characterize acute liver failure admissions in a Pediatric Intensive Care Unit of the portuguese pediatric livertransplantation center. To compare results before (A) and after (B) 2008.Material and Methods: Observational, retrospective study during a 20 year period (1994-2014). Inclusion criteria: age < 18 years old and acute liver failure (INR ≥ 2 without vitamin K response and hepatocellular necrosis). Children with previous liver disease were excluded.Results: Fifty children were included, with median age of 24.5 months. The most common etiology under 2 years old was metabolic (34.6%) and above that age was infectious (29.2%). Forty six percent were submitted to liver transplantation and 78% of them survived. Overall mortality was 34%. Median referral time was 7 days in period A (n = 35) and 2 days in period B (n = 15; p = 0.006). Pediatric risk of mortality´s median was 14.7 in period A and 6.5 in B (p = 0.019). Mortality was 37% vs 26% in periods A and B, respectively (p = 0.474).Discussion and Conclusions: Overall mortality was similar to the observed in other European centers. Liver transplantation is in fact the most effective therapeutic option. After 2008, there was a reduction in referral time and cases severity on admission; however, mortality has not reduced so far.